Association between oral lesions and disease activity in lupus erythematosus. (31st October 2019) - Del Barrio‐Díaz, P.; Reyes‐Vivanco, C.; Cifuentes‐Mutinelli, M.; Manríquez, J.; Vera‐Kellet, C.
Abstract: Background: Mucosal involvement is frequently seen in cutaneous lupus erythematosus (CLE) and systemic lupus erythematosus (SLE). There is no consensus regarding the prevalence, and a wide range of lesions has been reported. Its prognostic significance is currently unknown and a matter of controversy. Objective: To classify oral lesions in lupus, evaluate their prevalence and assess their possible association with disease activity. Methods: We conducted a descriptive study between 2016 and 2017. A total of 150 lupus patients were matched by sex, age and smoking status with 151 healthy individuals. All subjects underwent a careful evaluation of oral mucosa. On the same day of the clinical assessment, each patient underwent a peripheral venous blood and urine analysis. All patients underwent a full medical history, physical examination and a careful examination of the oral cavity. For each one, we obtained photographs of ten areas of the oral cavity. Two dermatologists of our group blindly recorded the presence and morphology of oral lesions. The disease activity of CLE patients was scored using the Revised Cutaneous Lupus Erythematosus Disease Area and Severity Index, and in SLE patients, activity was measured using the Systemic Lupus Erythematosus Disease Activity Index. Results: In CLE patients, there was a statistically significant correlation between higher cutaneous disease activity and the following oral findings: discoid plaques, cobblestone and red/brown‐pigmented macules. In patients with CLE, red macules on jugal mucosa were statistically associated with anaemia and positive antinuclear antibodies titres; additionally, the presence of gingivitis was related to systemic inflammation. In SLE patients, gingival telangiectases were statistically significantly associated with leucopenia, hypocomplementemia and systemic inflammation. Limitations: Biopsies on mucosal lesions were not performed. Conclusion: Some specific oral lesions correlate with disease activity in CLE and SLE.